2000
DOI: 10.1021/la0006770
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of Short-Chain Poly(ethylene oxide) Lipopolymers at the Air−Water Interface:  A Combined Film Balance and Surface Tension Study

Abstract: The interfacial behavior of a short-chain poly(ethylene oxide) (PEO) lipopolymer, PEO (molecular weight 2000) grafted distearoylphosphatidylethanolamine (PEO2K-DSPE), and its mixtures with distearoylphosphatidylcholine (DSPC) have been studied using Langmuir film balance and surface tension methods. Surface pressure-area isotherms for pure PEO2K-DSPE and PEO2K-DSPE/DSPC mixtures (with 2, 5, 10, 15, or 20 mol % of PEO2K-DSPE) revealed two phase transitions. The simple additivity in the molecular area of lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 21 publications
8
83
0
Order By: Relevance
“…These values are in agreement with the tendency reported by Xu and co-workers [23]. The collapse condition was corroborated by means of repeating of the isotherms before and after the collapse point.…”
Section: Resultssupporting
confidence: 92%
“…These values are in agreement with the tendency reported by Xu and co-workers [23]. The collapse condition was corroborated by means of repeating of the isotherms before and after the collapse point.…”
Section: Resultssupporting
confidence: 92%
“…49 The higher flexibility and mobility of low MW PEG chains result in higher entropic repulsion between proteins and the surface. 50,51 Our in vitro studies confirmed the choice of PEG 5 kDa for passivation coatings of ICG-NCs and for impeding their uptake by macrophages. 10 Conversely, reduced flexibility of high MW PEG chains, due to the entrapment submit your manuscript | www.dovepress.com of long chains, induces low protein resistivity.…”
Section: Discussionsupporting
confidence: 63%
“…Most fundamental studies on telechelic HM-polymers focus on the ''bulk" properties of their aqueous solutions, rather than on their interfacial characteristics. A number of reports demonstrate that PEO chains modified with hydrophobic substituents, such as n-alkyl [10], perfluoro [11], polyhedral oligomeric silsesquioxanes [12], or double-chained lipids [13] are able adsorb at the A/W interface upon end-group modification. Endmodified HM-poly(N-isopropylacrylamide) (PNIPAM) derivatives [14] also form Langmuir films at the A/W interface.…”
Section: Introductionmentioning
confidence: 99%